2021
DOI: 10.1021/acs.joc.0c02768
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Preparation of N-Acylbenzoxazines from Phenols, Nitriles, and DMSO Initiated by a Catalytic Amount of (COCl)2

Abstract: A convenient preparation method of N-acylbenzoxazines has been developed, in which phenols react with nitriles and dimethyl sulfoxide (DMSO) in the presence of a catalytic amount of (COCl)2 in CH3CN or chloroform to afford the corresponding N-acylbenzoxazines in moderate-to-good yields. DMSO acts as a source of HCHO, which is generated in situ from the decomposition of a methoxydimethylsulfonium salt. A regeneration cycle of the methoxydimethylsulfonium salt is proposed, which is initiated by a catalytic amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The combined reagent, DMSO/(COCl) 2 , is widely used as an oxidant for the oxidation of alcohols, in which the chlorodimethylsulfonium salt is the key active species [15] . In our recent studies about the application of sulfoxide/oxalyl halide in various transformations, it was found that DMSO/(COCl) 2 is quite versatile and can generate various active species in situ , such as CH 3 SCl, [16–18] HCHO, [19] or act as a source of Cl + [20] . We also established a practical preparation method of methyl methanethiosulfonate using DMSO in the presence of catalytic amount of (COCl) 2 [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The combined reagent, DMSO/(COCl) 2 , is widely used as an oxidant for the oxidation of alcohols, in which the chlorodimethylsulfonium salt is the key active species [15] . In our recent studies about the application of sulfoxide/oxalyl halide in various transformations, it was found that DMSO/(COCl) 2 is quite versatile and can generate various active species in situ , such as CH 3 SCl, [16–18] HCHO, [19] or act as a source of Cl + [20] . We also established a practical preparation method of methyl methanethiosulfonate using DMSO in the presence of catalytic amount of (COCl) 2 [21] .…”
Section: Introductionmentioning
confidence: 99%
“…We have been exploring new methodologies using the combination of sulfoxide/(COX) 2 in various organic transformations recently. Several synthetic methods have been developed, [15] including sulfenyllactonization [15a] or chlorolactonization [15b] of alkenoic acids, bromination of alkenes, [15c] dehydration of primary amides or aldoximes, [15d] dichlorination of alkenes, [15e] and the preparation of benzoxazines [15f] . Encouraged by the results of chlorolactonization of alkenoic acids and dichlorination of alkenes with Ph 2 SO/(COCl) 2 , we envisioned that it might be practical for the chlorination of 1,3‐dicarbonyls with sulfoxide/(COCl) 2 .…”
mentioning
confidence: 99%